2016
DOI: 10.1002/cae.21727
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of an interactive virtual control laboratory using haptic interface for undergraduate engineering students

Abstract: In most engineering courses, students need to experience the theoretical issues discussed in the classrooms to gain a deeper understanding. The high cost of laboratory equipment deprives many educational institutions of delivering quality education. Virtual laboratories can alleviate this problem substantially. Virtual laboratories with audiovisual and force feedback make the understanding and analysis of many engineering courses possible. This paper presents the design and implementation of an interactive vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
(37 reference statements)
0
13
0
1
Order By: Relevance
“…Furthermore, local practical activities have been demonstrated to be efficient when engineering students acquire analysis skills. Therefore, experimentation has gained more popularity as advances in digital technology enable teachers to implement practical learning activities, and for students to create their own knowledge by developing realistic experiments .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, local practical activities have been demonstrated to be efficient when engineering students acquire analysis skills. Therefore, experimentation has gained more popularity as advances in digital technology enable teachers to implement practical learning activities, and for students to create their own knowledge by developing realistic experiments .…”
Section: Resultsmentioning
confidence: 99%
“…• El uso de Internet permite la experimentación asíncrona, ampliando la oferta de horarios para el estudiante en formación, de modo que sea un proceso de interacción mucho más fácil [6,9]. • Permite al estudiante conocer elementos físicos de un laboratorio real o una instalación física cuando el acceso a ellos sea limitado.…”
Section: Laboratorios Virtuales En El Proceso De Enseñanza-aprendizajeunclassified
“…In engineering, one of the most popular subject areas for virtual laboratories is control systems. In the literature, a virtual control laboratory was developed for students to design and simulate classical proportional‐integral‐derivative (PID) controllers and fuzzy logic controllers (FLC) ; a simulation platform using MATLAB and Simulink was developed to investigate the performance of quadcopters using self‐tuning fuzzy PID controllers ; an interactive virtual control laboratory that provides haptic interfaces to students was developed to teach classical control systems and advanced topics such as impedance control and fuzzy control ; a remote laboratory that allows students to access real industrial equipment through the Internet was reported in Ref. .…”
Section: Introductionmentioning
confidence: 99%